2015
DOI: 10.1097/ana.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Equivolume, Equiosmolar Solutions of Hypertonic Saline and Mannitol for Brain Relaxation in Patients Undergoing Elective Intracranial Tumor Surgery

Abstract: Our results suggest that HTS provides better brain relaxation than mannitol during elective intracranial tumor surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…By contrast, mannitol infusion could induce hypovolaemia through an increase in diuresis [13,[20][21][22][23][24][25]28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, mannitol infusion could induce hypovolaemia through an increase in diuresis [13,[20][21][22][23][24][25]28]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent guidelines suggest the use of HTS as a second-line therapy in cases where mannitol fails to reduce ICP [8]. Despite hyperosmolar solutions being routinely used in neurosurgical and neurocritical care (NCC) patients for brain relaxation and ICP management [8][9][10][11][12][13][14], there is scanty information on the time course of their haemodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Besides the mechanism of osmotic dehydration, HS also has the effect of antibrain edema through the mechanism of non-osmotic dehydration, such as antiinflammatory. 8,21 In recent years, it has been found that the crosstalk between microglia and astrocytes plays a central role in regulating inflammation in the brain. Activated microglia can release inflammatory factors (ie, IL-1β), which can activate astrocytes and upregulate glial fibrillary acidic protein (GFAP) expression.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports exist documenting a potentially more beneficial effect in reducing ICP associated with hypertonic saline as compared with mannitol. 34,35 Administration of furosemide (0.7 mg/kg) before administration of mannitol has a synergistic effect in lowering ICP. Currently, there is no evidence to support that mannitol is contraindicated in cases of intracranial hemorrhage, as has previously been suggested.…”
Section: Fluid Therapymentioning
confidence: 99%